2022
DOI: 10.1186/s12885-022-10395-9
|View full text |Cite
|
Sign up to set email alerts
|

Complications of radical hysterectomy with pelvic lymph node dissection for cervical cancer: a 10-year single-centre clinical observational study

Abstract: Background and purpose The complications of radical surgery for cervical cancer can increase patient suffering and affect their quality of life. This retrospective study assessed the safety of radical hysterectomy (RH) with pelvic lymph node dissection (PLND) by observing the complications of patients with cervical cancer who underwent this procedure in a single centre over 10 years. Our findings may provide experience and evidence for preventing and reducing complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, there were no significant associations between any disease, procedure or patients' characteristics and the occurrence of adverse surgical outcomes. These findings contrast with what is reported in literature by many authors who describe factors like FIGO stage IB, parametrial invasion, advance age of the patient, tumor size like predictors of complications [27]. Some studies suggest that when minimal invasive surgery is used, there is reduced hospital stay, hemorrhagic complications and pelvic pains but both the short term and long term complications are comparable for the 2 approaches [28].…”
Section: Discussioncontrasting
confidence: 61%
“…However, there were no significant associations between any disease, procedure or patients' characteristics and the occurrence of adverse surgical outcomes. These findings contrast with what is reported in literature by many authors who describe factors like FIGO stage IB, parametrial invasion, advance age of the patient, tumor size like predictors of complications [27]. Some studies suggest that when minimal invasive surgery is used, there is reduced hospital stay, hemorrhagic complications and pelvic pains but both the short term and long term complications are comparable for the 2 approaches [28].…”
Section: Discussioncontrasting
confidence: 61%
“…Functional disorders are the most commonly reported complications and are thought to be caused by the disruption of sympathetic and parasympathetic nerves during the resection of posterior, anterior and lateral parametria, which run towards the bladder and rectum in the inferior portion of uterosacral ligaments, cardinal ligaments and bladder pillars [8][9][10]. Therefore, the most common symptoms in the first year after surgery are bladder atony and urinary retention [11]. Bladder dysfunction has been reported to occur in up to 47% of cases [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogens of urinary tract infection varied during JJ stent indwelling. About 20.83% (5/24) patients experienced two different kinds of pathogens and 12.50% (3/24) patients experienced ≥ three kinds of pathogens (Table 3 & 4). Results from the antibiotic sensitivity analysis of Escherichia coli (Ecoli), the most common pathogen of urinary tract infections, demonstrated that Ecoli was resistant to Ampicillin, Ceftriaxone, Cefotaxime, Cefazolin and Cefuroxime.…”
Section: Distribution Of Pathogens Of Urinary Tract Infection In the ...mentioning
confidence: 99%